A Case of Lionfish Envenomation Presenting to an Inland Emergency Department. (13th August 2017) - Schult, Rachel F.; Acquisto, Nicole M.; Stair, Crystal K.; Wiegand, Timothy J.
Abstract : Lionfish envenomation can cause erythema, edema, necrosis, and severe pain at the exposed site. Treatment often includes supportive wound care, pain management, and hot water immersion. We report a case of lionfish exposure presenting to an inland emergency department treated successfully with these measures.